Editorial note - Assounga, Alain (African Journal of Nephrology, 2017)
In this issue of African Journal of Nephrology (AJN), and on behalf of the editorial board, I am pleased to announce the transition of our journal from being a paper and e-mail based submission journal to being a completely web-based submission journal. The web submission is handled by the website www.journals.ac.za/index.php/ajn, and a link from the previous AJN website to the new one will be maintained for six months. The transition from email submission to a web page submission started in August 2016. I am also delighted to welcome a new editorial board which is starting a two-year appointment. The list of the new board members is available on the AJN website. These housekeeping points addressed, I wish to give a preview of the content of this issue. As in our previous issues, this one covers a wide variety of topics. Transplantation is covered through a paper by Dr Rashad et al. entitled IL-10 gene polymorphism and graft outcome in live-donor kidney transplantation in Egypt. This is an important paper as the genetic make-up of a given population is unique. Hence, understanding the intricacy of genetics and disease in Africa is a relevant subject as any disease elsewhere may not have the same expression in Africa. Furthermore, pharmacogenomics may lead to a diversity of response to treatment. Thus, findings of studies from one region of the world may or may not be relevant in another part of the world. Finally, Dr Chothia et al. report on a case of Renal cortical necrosis following abdominal surgery and highlight the role of vascular thrombosis. The second part of this issue of AJN contains abstracts of the South African Renal Congress 2016 which was held in Cape Town from 9 to 11 September 2016 at the Century City Conference Centre. The overall theme of the congress was “Transitions in Nephrology”. Dr Julian Jacobs, the congress organiser, opened the congress by welcoming delegates, and highlighted the themes addressed in the congress. The abstracts of the Congress covered all aspects of nephrology while highlighting the transitional aspects of each topic. The main topics included HIV nephropathy, the controversy in the use of vitamin D in renal patients, and so forth. Preventative aspects of nephrology were addressed by Professor AM Meyers who presented the results of the NKFS Schools Survey. The Discovery Health KidneyCare Programme was also presented. Studies on various topics including lupus nephritis, as well as factors for progression of CKD have been reported on. Transplantation papers include the outcome of antibody mediated allograph rejection by M Davies, whereas haemodialysis was represented by dialysis adequacy, and a nutrition abstract by Dr Mashabane. HIV and peritoneal dialysis was covered by Dr K Ndlovu’s report on the presence of HIV particles in PD effluent. Van Biljon et al. reported on the challenge of CKD management in children in Gauteng. Professor A Assounga Editor-in-chief